2002
DOI: 10.1046/j.1365-2230.2002.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of class I HLA antigens with the clinical manifestations of Turkish patients with Behçet's disease

Abstract: Genetic factors appear to be important in the pathogenesis of Behçet's disease. Although it is known to be strongly associated with HLA-B 51, the association of HLA class I antigens with specific clinical findings of the disease has not been studied extensively and the few studies are conflicting. The aim of this study was to investigate the association of HLA class I alleles with the manifestations of Behçet's disease in Turkish patients. Eighty-five patients with Behçet's disease were typed for HLA-A, B, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
4
22
2
Order By: Relevance
“…Members of this group share the amino acid alanine at position 26, which contributes to the structure of peptide-binding pocket B and determines the motif of bound peptides [16]. In this study, we found three HLA-B alleles different from others studies in which the HLA-B * 51 allele has been associated consistently in Turkish, Korean, Greek, Japanese, Israel Arabs, Iranian, Italian, and Moroccan patients [17][18][19][20][21][22][23][24]. These alleles, in Mexicans, might be the equivalent of HLA-B51 found in the above mentioned populations.…”
Section: Discussioncontrasting
confidence: 49%
“…Members of this group share the amino acid alanine at position 26, which contributes to the structure of peptide-binding pocket B and determines the motif of bound peptides [16]. In this study, we found three HLA-B alleles different from others studies in which the HLA-B * 51 allele has been associated consistently in Turkish, Korean, Greek, Japanese, Israel Arabs, Iranian, Italian, and Moroccan patients [17][18][19][20][21][22][23][24]. These alleles, in Mexicans, might be the equivalent of HLA-B51 found in the above mentioned populations.…”
Section: Discussioncontrasting
confidence: 49%
“…Although the pathogenesis is not exactly known, it is believed to be triggered by microbial or environmental factors, with a genetic predisposition. In many ethnic groups that settled along the ancient Silk Road, a significant relationship is detected between BD and HLA-B51positivity (Kaya et al, 2002;Kötter et al, 2004;de Menthon et al, 2009;Song and Kang, 2012;Hughes et al, 2013;Houman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese Han patients, B 5101 dominated, and a new as sociation between BD and HLA-B 46 was found. Remarkably, in Turkish, Jordanian, Iranian and Japanese BD patients, the whole nucleotide sequences of HLA-B 510101 genes, with the promoter and intron regions, are identical, proposing that B 510101 may have the same phylogenetic source [22][23][24][25][26][27][28][29][30][31].…”
Section: Genetic Susceptibility Of Behçet's Diseasementioning
confidence: 99%